Influence of Nanocellulose Additive on the Film Properties of Native Rice Starch-based Edible Films for Food Packaging - Jeevahan, Jeya; Chandrasekaran, Manoharan (Recent Patents on Nanotechnology, 2019)
Background & Objective: Starch-based edible films, which are transparent, odourless, biodegradable, tasteless, and semi-permeable to gases and food additives, have attracted the attention of the research community as the alternative food packaging materials to synthetic plastics. However, they pose poor water resistance and mechanical strength that should be improved for food packaging application. Few relevant patents to the topic have been reviewed and cited. Methods: Inclusion of nanoadditives in starch films can not only improve their mechanical and barrier properties but also can act as antimicrobial agent, oxygen scavenger, and biosensor. The present investigation is focussed on the effects of nanocellulose extracted from banana pseudostems on the film properties of rice starch-based edible films. Nanocellulose was extracted from dried banana pseudostems through isolation of cellulose and acid hydrolysis. Rice starch-based edible films were prepared through solution casting by adding nanocellulose of varying concentrations (0%, 2%, 4%, 6%, 8% & 10%). Results: The film properties, such as Water Vapour Permeability (WVP), mechanical strength (tensile strength, Young's modulus and percentage of elongation), film solubility in water and film colour, were determined. The test results were discussed and the effects of nanocellulose additives were studied. Conclusion: From the results, it was clear that the addition of nanocellulose had improved the film properties, making the rice starch-based edible films a promising choice for food packaging applications.
Keywords: water vapour permeability